Doxorubicin impairs cognitive function by upregulating AMPAR and NMDAR subunit expression and increasing neuroinflammation, oxidative stress, and apoptosis in the brain - Alhowail, Ahmad H.; Aldubayan, Maha A. (Frontiers in Pharmacology, 2023)
Introduction: The anticancer drug doxorubicin (DOX) is used for various malignancies. However, it also causes cognitive impairment in cancer survivors. In order to determine the mechanisms underlying the acute effects of DOX, we assessed the mRNA and protein expression of glutamate receptors and proteins involved in cognitive function and apoptosis. Methods: Fear-conditioning memory tests were performed in rats after a single intraperitoneal injection of DOX (25 mg/kg) to evaluate short-term memory function. Rat brain samples were collected, and GluA1 mRNA and protein expression; NR2A and NR2B mRNA expression; and COX-2, NF-kB, TNF-α, and MDA, Bax, and caspase-3 levels were assessed via reverse transcription polymerase chain reaction and enzyme-linked immunosorbent assays. Results: We observed a decreased number of entries in Y-maze, decreased exploration time to the novel object in the novel object recognition (NOR), and decreased freezing time in the fear-conditioning memory tests in DOX-treated rats relative to those in control rats, demonstrating cognitive impairment. GluA1, NR2B, and NR2A expression and MDA, NF-κB, Bax, COX-2, TNF-α, and caspase-3 levels in the brain were significantly elevated in DOX-treated rats. Conclusion: DOX induced cognitive impairment in the rats via neuronal toxicity by upregulating AMPAR and NMDAR expression and increasing neuroinflammation, oxidative stress, and apoptosis in the brain.